Understanding C++ for MFC - Raposa, Richard F. (CMP Books, 2001)
Jumpstart your MFC programming without the tedious study of C++! Now you can learn C++ and MFC together -- learning C++ principles on a need-to-know basis. Author Richard Raposa has refined this tutorial over years of teaching Windows programming in quick-start environments. You will learn: · C++ essentials · object-oriented programming (OOP) fundamentals · how to create Windows programs using Visual C++ and MFC Demonstration projects will give you a contextual understanding of the C++ features that are prerequisite to OOP programming including encapsulation, inheritance and polymorphism. Once you understand these, the task of learning MFC and Windows programming becomes much easier. So, if you want to take advantage of MFC's power and efficiency in creating full-scale, sophisticated Window applications but have no C++ or Windows programming experience ... or if you are accustomed to programming at the Win32 API level and want to take advantage of MFC's shorter and easier program development ... this is the book for you. Richard F. Raposa has a Ph.D. in mathematics and more than a decade of experience teaching mathematics and computer science in both university and industrial training programs. Richard has won numerous university teaching awards and is a Sun Certified Instructor, Sun Certified Programmer, Microsoft Certified Professional and Microsoft Certified Instructor. He provides custom C++, Java and other OO training solutions through JLicense, Inc., his training firm based in Rapid City, S.D.